CHARACTERISTICS TOIMPERSONAL STATE OF MIND IN PHILOSOPHY P. AVSENYEVA - Поперечна, Г. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
For the characteristics of the unconscious states of the soul in P. Avseniev’s philosophy. The article is dedicated to analysis of P. Avseniev’s points of view on the correlation of sleep and wake of a soul in human’s livelihoods, to the meaning of dreams in the process of self-knowledge, and also to the causes and essence of insanity and possibilities of the hypnotic state. Key words: soul, heart, wake, sleep, dream, insanity, magnetism.